2022
DOI: 10.3390/applmicrobiol2010011
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Biology of Thermophiles: Taking Bioengineering to the Extremes?

Abstract: Synthetic biology applications rely on a well-characterized set of microbial strains, with an established toolbox of molecular biology methods for their genetic manipulation. Since there are no thermophiles with such attributes, most biotechnology and synthetic biology studies use organisms that grow in the mesophilic temperature range. As a result, thermophiles, a heterogenous group of microbes that thrive at high (>50 °C) temperatures, are largely overlooked, with respect to their biotechnological potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…The range of optimum activity temperatures for invertase varies widely in the literature. However, thermostable enzymes are generally preferred for industrial applications 32 . Therefore, the invertase reported here is a potential industrial enzyme, considering its optimum temperature and thermal stability.…”
Section: Discussionmentioning
confidence: 99%
“…The range of optimum activity temperatures for invertase varies widely in the literature. However, thermostable enzymes are generally preferred for industrial applications 32 . Therefore, the invertase reported here is a potential industrial enzyme, considering its optimum temperature and thermal stability.…”
Section: Discussionmentioning
confidence: 99%
“…The survival ability of this thermophilic microorganism is related to its cell structure which has several advantages (Vavitsas et al, 2022);(Sohlenkamp & Geiger, 2016); (Wang et al, 2021) Cell membrane structure (Cebrián et al, 2017); (Parrilli et al, 2022); Chaperonins (Novik et al, 2019); (Villain et al, 2022); (Singh et al, 2021) Structure of DNA gyrase…”
Section: Sourcesmentioning
confidence: 99%
“…High temperature exerts a fundamental stress on biological systems by destabilizing proteins, membranes, and other molecules (16). Tolerating this stress has driven evolution since life began (17), is relevant to understanding the response of pathogens to fever (18), could be helpful to engineer more efficient cell factories (19), and will become a more common selection pressure as global warming continues (20). One prior study demonstrated the presence of epistasis among mutations acquired under this stress (21).…”
Section: Introductionmentioning
confidence: 99%